Effect of Accounting Knowledge, Accounting Training, Business Scale, and Business Experience on the Use of Accounting Information in UMKM - Melinda, Dian; Wiralestari, Wiralestari; Mansur, Fitrini (PT. Riset Press International, 2025)
This study aims to determine the effect of accounting knowledge, accounting training, business scale, and business experience on the use of accounting information in MSMEs in Jambi City. This study uses quantitative methods with data taken in the form of primary data. The population in this study were MSME actors in 2023, with a total of 50,747. The sample size to be studied from a population can be used with the Slovin approach formula. The sampling technique uses the Cluster Random Sampling method. The data collection technique is using a questionnaire. The application to help complete the proposed data analysis uses Statistical Package for Social Sciens (SPSS) 26 software. The results of the data analysis conducted by this researcher show that accounting knowledge partially has a significant effect on the use of accounting information. Accounting training partially has no effect and is significant to the use of accounting information. Business scale partially has a significant effect on the use of accounting information. Business experience partially has a significant effect on the use of accounting information. Accounting knowledge, accounting training, business scale, and business experience are significantly related to the use of accounting information.